Identification of a novel founder variant in DNAI2 cause primary ciliary dyskinesia in five consanguineous families derived from a single tribe descendant of Arabian Peninsula - Al-Mutairi, Dalal A.; Alsabah, Basel H.; Alkhaledi, Bashar A.; Pennekamp, Petra; Omran, Heymut (Frontiers in Genetics, 2022)
Abstract Introduction: Primary ciliary dyskinesia (PCD) is caused by dysfunction of motile cilia resulting in insufficient mucociliary clearance of the lungs. The overall aim of this study is to identify disease causing genetic variants for PCD patients in the Kuwaiti population. Methods: A cohort of multiple consanguineous PCD families was identified from Kuwaiti patients and genomic DNA from the family members was analysed for variant screening. Transmission electron microscopy (TEM) and immunofluorescent (IF) analyses were performed on nasal brushings to detect specific structural abnormalities within ciliated cells. Results: All the patients inherited the same founder variant in DNAI2 exhibited PCD symptoms. TEM analyses demonstrated lack of outer dynein arms (ODA) in all analysed samples. IF analysis confirmed absence of DNAI1, DNAI2 and DNAH5 from the ciliary axoneme. Whole exome sequencing, autozygosity mapping and segregation analysis confirmed that seven patients carry the same homozygous missense variant (DNAI2:c.740G>A; p.Arg247Gln; rs755060592). Conclusions: DNAI2:c.740G>A is the founder variant causing PCD in patients belonging to a particular Arabian tribe which practices consanguineous marriages.